TRANSFERÊNCIA DE CONHECIMENTO EM REDES INTERORGANIZACIONAIS: estudo de caso APOMEL – Associação dos Produtores de Mel de Ortigueira - Krysa, Agenor Felipe (2018)
This paper has as a field of study the relationships that occur in the ambit of interorganizational networks. The objective of this research is to contribute to this field of study by understanding the contribution of the networks to the process of knowledge transferring among the producers associated with APOMEL, Ortigueira Honey Producers Association, founded in the city of Ortigueira, northwest region of the State of Paraná, conducted on the optics of networks and considering it, a locus of knowledge transfer among its actors. This association is a private non-profit entity and has 57 associates who are beekeepers in the municipality of Ortigueira and region. It was founded in the year of 1984 by initiative of a support organization, and since then it has been managed by its associates. The choice of this theme is justified by the results obtained by APOMEL throughout its history, and by the productive potential of the region, being recognized for its unique characteristics of production and quality, becoming a national reference in honey production. Thus, the origin of the studies in networks, definitions and concepts, were first approached to present the approaches for understanding in networks and the process of knowledge transfer in interorganizational networks. In order to achieve the proposed objectives, the case study was adopted as a research strategy, APOMEL was used as the object of studies, by focusing on their relationships. The understanding of the phenomenon occurred through the combination of quantitative and qualitative methods, in an inductive way. The application of the quantitative research instruments resulted in the construction of a sociogram representative of the network relations, and with the support of the UCINET © software, it was possible to map and understand the relational structures that make up APOMEL. Using the content analysis of documents, texts and reports, interview transcripts and field observations, the process of knowledge transfer, and the facilitating and inhibiting factors of network knowledge exchanges, were described. The analysis of the process of knowledge transfer in the network established among the associated producers concludes that: I) APOMEL is directly linked to its support entities; II) The actors of the support entities, members of the board of directors and the previous president of APOMEL have privileges in terms of centrality and potential access in the network; III) The technical consultant is the main source for obtaining knowledge in the network; IV) Knowledge issues are planned and coordinated by the support entities; V) The network does not present a high level of density, however I present a high level of connectivity, facilitating the flow of information and knowledge; VI) There is a lack of trust among the members, consequently, the other facilitating characteristics for the exchange of knowledge are affected; VII) Monthly meetings are the main means for the establishment of contacts and communication; VIII) Courses, consultancies and field days are the main sources of knowledge transfer in the network; IX) The current governance is an action of resistance and reaction of a group dissatisfied with the actions from the past. These findings allowed the researcher to recommend to APOMEL that as a network, strengthen the bonds of trust among its members, seeking to generate moments of interaction and exchange of knowledge, reducing the role of the support entities.